Seed Priming Improved Antioxidant Defense System and Alleviated Ni-Induced Adversities in Rice Seedlings Under N, P, or K Deprivation - Khan, Fahad; Hussain, Saddam; Khan, Sehrish; Geng, Mingjian (Frontiers in Plant Science, 2020)
Excess nickel (Ni) concentration in the growing medium severely hampers the plant growth by disturbing oxidative metabolism and nutrient status. The present study was carried out to investigate the individual and interactive effects of Ni toxicity (0.25 mM NiSO4.6H2O) and nutrient deprivation (no-N, no-P, or no-K) on growth, oxidative metabolism, and nutrient uptake in primed and non-primed rice seedlings. Rice seed was primed with distilled water (hydropriming), selenium (5 mg L-1), or salicylic acid (100 mg L-1). The Ni toxicity and deprivation of N, P, or K posed negative effects on the establishment of rice seedlings. The shoot length and fresh biomass were severely reduced by Ni toxicity and nutrient stresses; the minimum shoot growth was recorded for rice seedlings grown under Ni toxicity and no-N stress. The Ni toxicity reduced the root fresh biomass but did not significantly affect the root length of N-deprived seedlings. The rice seedlings with no-P or no-K recorded similar root fresh biomass compared with those grown with sufficient nutrient supply. The Ni toxicity alone or in combination with nutrient stresses triggered the production of reactive oxygen species (ROS) and caused lipid peroxidation in rice seedlings. Among antioxidants, only glutathione reductase and vitamin E were significantly increased by Ni toxicity under different nutrient stress treatments. The Ni toxicity also reduced the concentrations of N particularly in shoot of rice seedlings. The N-deprived (no-N) seedlings recorded maximum Ni concentration in shoot, while K-deprived (no-K) seedlings showed higher Ni concentrations in root. Seed priming with selenium or salicylic acid was effective to alleviate the detrimental effects of Ni toxicity and/or nutrient stresses on rice seedlings. The better growth and greater stress tolerance of primed seedlings was coordinately attributed to lower ROS production, higher membrane stability, strong antioxidative defense system, and maintenance of mineral nutrient status.